2007
DOI: 10.2298/abs0702113s
|View full text |Cite
|
Sign up to set email alerts
|

Of chronic diazepam treatments on behavior on individually housed rats

Abstract: The present study analyzed the effects of chronic treatment with low doses of diazepam on body weight, defecations and urinations, vertical rears, the elevated platform test, and self-grooming in male rats exposed for 21 days to social isolation. The rats were treated for 21 days with diazepam (0.2 mg/kg, i.p) or its vehicle. Social isolation led to decreased body weight and vertical rears, more defecations and urinations, increased reluctance to step down from the test platform, shorter duration of grooming, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…The standard drug diazepam controlled the metabolic alterations and gastric ulcers in CMS rats indicate the GABAergic role in CMS induced physiological alterations. Earlier reports indicated that diazepam reversed the stress induced non-grooming and grooming behaviour and gastric ulcers in rats [ 33 , 34 ] which supports our present findings. Further, diazepam reversed the CMS induced behavioural alterations and showed anxiolytic activity in open field test, antidepressant activity in behavioural despair test.…”
Section: Discussionsupporting
confidence: 93%
“…The standard drug diazepam controlled the metabolic alterations and gastric ulcers in CMS rats indicate the GABAergic role in CMS induced physiological alterations. Earlier reports indicated that diazepam reversed the stress induced non-grooming and grooming behaviour and gastric ulcers in rats [ 33 , 34 ] which supports our present findings. Further, diazepam reversed the CMS induced behavioural alterations and showed anxiolytic activity in open field test, antidepressant activity in behavioural despair test.…”
Section: Discussionsupporting
confidence: 93%
“…Our results agree with several social isolation studies that reported: anxiety-like behaviour after isolation in early stages of development [45,[48][49][50][51][52][53][54], in adolescence [55][56][57], and also -but less described-in adulthood [22,47]. Moreover, chronic adult isolation reduced the duration of grooming and caused more urination and defecation [58]. Social deprivation is a potent emotional stressor, and it can alter the correct functioning of the immune and neuroendocrine systems [7].…”
Section: Discussionsupporting
confidence: 91%
“…The fact that chronic isolation did not affect locomotor activity or grooming could perhaps be explained by the duration of stress which lasted for only 3 weeks. Some other authors reported that longer periods of isolation could result in hyperlocomotion [33] as well as in altered quality (order and duration of single sequences), but not frequency, of grooming [34]. …”
Section: Discussionmentioning
confidence: 99%